1998
DOI: 10.1088/0954-3899/24/1/024
|View full text |Cite
|
Sign up to set email alerts
|

Muons in extensive air showers: III. Primary mass composition studies

Abstract: The extensive air shower muon-density and time-spread measurements made over many years at Haverah Park are discussed in relation to the mass composition of primary cosmic rays covering the primary energy range from 5 × 10 14 to more than 10 19 eV. At energies above 3 × 10 15 eV the measurements seem to indicate an unchanging primary-mass composition up to 10 19 eV. At energies below the 'knee' however the results indicate a move from heavier to lighter primaries with increasing energy. There is support for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The most popular interpretation of the knee has been the existence of a knee in the primary cosmic ray energy spectrum at an energy of about 3-5 × 10 6 GeV and, as a possible consequence, the change of the mass composition. There are different experimental analyses leading to opposite conclusions concerning the primary composition after the knee (lighter [2], normal [3,4] or heavier [5][6][7]).…”
Section: Introductionmentioning
confidence: 99%
“…The most popular interpretation of the knee has been the existence of a knee in the primary cosmic ray energy spectrum at an energy of about 3-5 × 10 6 GeV and, as a possible consequence, the change of the mass composition. There are different experimental analyses leading to opposite conclusions concerning the primary composition after the knee (lighter [2], normal [3,4] or heavier [5][6][7]).…”
Section: Introductionmentioning
confidence: 99%
“…Several Extensive Air Shower (EAS) measurements (till now the study of cosmic rays above 1 PeV has been of an indirect nature via EAS observations) have been made to determine the mass composition of cosmic rays in the energy region of interest, but the measurements have not yielded mutually consistent results yet due to the weak mass resolution of the measured shower observables (Haungs 2011). Most of the findings (Navarra 1998;Glasmacher et al 1999;Aartsen et al 2013;Fomin et al 1996) based on electron content relative to muon content (or vice versa) in EAS suggest that composition becomes heavier with energy beyond the knee, though the Haverah Park experiment and a few other observations (particularly underground muon telescopes) (Blake & Nash 1998Danilova et al 1995;Saha et al 1998;Aglietta et al 1990;Ahlen et al 1992;Kasahara et al 1997;Longley et al 1995;Bakatanov et al 1999) found the opposite trend for mass composition. Mass composition estimated from the measurement of the depth of shower maximum through observation of Cerenkov (Boothby et al 1997;Swordy & Kieda 2000;Fowler et al 2001;Chernov et al 2005;Karle et al 1995;HEGRA-Collaboration et al 2000;Dickinson 1999;Efimov & et al 1991) or fluorescence radiation (Abraham et al 2010;Abbasi et al 2008Abbasi et al , 2004Tsunesada 2011;Jui & Telescope Array Collaboration 2012), on the other hand, suggests a lighter mass composition beyond the knee differing from that obtained with muon to electron content ratio (Haungs 2011;Hörandel 2013;Bhadra & Sanyal 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several Extensive Air Shower (EAS) measurements (till now the study of cosmic rays above 1 PeV is of indirect nature via the EAS observations) have been made to determine the mass composition of cosmic rays in the concerned energy region but the measurements have not yielded mutually consistent results yet due to the weak mass resolution of the measured shower observables [48]. Most of the findings [1,40,47,66] based on electron content relative to muon content (or vice versa) in EAS suggest that composition becomes heavier with energy beyond the knee though Haverah Park and few other observations (particularly underground muon telescopes) [5,6,14,20,21,27,31,59,64] found opposite trend of mass composition. Mass composition estimated from measurement of the depth of shower maximum through observation of Cerenkov [13,23,29,35,36,41,58,78] or fluorescence radiation [2-4, 55, 81] on the other hand suggest lighter mass composition beyond the knee differing from those obtained with muon to electron content ratio [17,48,52].…”
Section: Introductionmentioning
confidence: 99%